Consumption smoothing channels in open economies - Asdrubali, Pierfederico; Kim, Soyoung (Journal of Banking & Finance, 2009)
Many intertemporal open economy macro models imply a theory of consumption smoothing channels; thus we build an empirical model to analyze the intertemporal smoothing role of saving components (fixed investments, inventories and trade balance) through the use of VAR impulse responses to different types of shocks. We find that for the OECD countries the bulk of intertemporal smoothing has been carried out domestically, via gross fixed investments and inventories, but the trade balance has also played a relevant – albeit volatile – smoothing role. We also characterize the dynamic behavior of each component: the trade balance and inventories are mostly used as short-run smoothing tools while fixed investment provides more and more smoothing over time. We can also address some empirical puzzles, such as the “excess sensitivity of investment” anomaly (Glick, R., Rogoff, K., 1995. Global versus country-specific productivity shocks and the current account. Journal of Monetary Economics, 35, 159–192) and the “saving-investment correlation puzzle” (Feldstein, M., Horioka, C., 1980. Domestic saving and international capital flows. Economic Journal, 90, 314–329).